2018
DOI: 10.1007/s10880-018-9560-0
|View full text |Cite
|
Sign up to set email alerts
|

Poor Self-efficacy for Healthcare Provider Interactions Among Individuals with HIV-Associated Neurocognitive Disorders

Abstract: Two factors that influence HIV health behaviors and therefore may contribute to gaps in the HIV treatment continuum are poor health-related self-efficacy and HIV-associated neurocognitive disorders (HAND). However, the relationship between HAND and self-efficacy has not been assessed. In an HIV sample, 91 individuals with intact cognition (HAND-) and 40 individuals with HAND (HAND+) were administered a measure of self-efficacy for healthcare interactions with providers. Participants with HAND had significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
3
6
0
1
Order By: Relevance
“…A major finding from this study is that health literacy capacity appears to mediate the relationship between neurocognition and eHealth literacy in the setting of HIV disease. These data support the idea that health literacy capacity (viz., knowledge, numeracy, and understanding) is dependent in part on neurocognitive functioning (e.g., learning), as has been shown in prior studies from our group (e.g., [25][26][27]. Importantly, however, the relationship between neurocognition and perceived eHealth literacy is explained by health literacy capacity.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A major finding from this study is that health literacy capacity appears to mediate the relationship between neurocognition and eHealth literacy in the setting of HIV disease. These data support the idea that health literacy capacity (viz., knowledge, numeracy, and understanding) is dependent in part on neurocognitive functioning (e.g., learning), as has been shown in prior studies from our group (e.g., [25][26][27]. Importantly, however, the relationship between neurocognition and perceived eHealth literacy is explained by health literacy capacity.…”
Section: Discussionsupporting
confidence: 67%
“…In 2010, Waldrop-Valverde et al (24) demonstrated that lower memory, attention, and complex visuomotor sequencing were independently associated with poorer health-related comprehension and numeracy in HIV. Subsequent research revealed that individuals with HAND are at risk for low health literacy, ranging from fundamental skills like numeracy (25) to higher-order capacities, such as medical decision-making (26) and engagement with healthcare providers (27). Moreover, standard measures of health literacy relate to performance-based health-related Internet navigation skills among persons with HIV disease (9).…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study also indicate that poorer performance on measures of health literacy and global neurocognition is uniquely associated with lower selfefficacy for HCP interactions, respectively. These findings are consistent with previous research that identified neurocognitive impairment (Morgan et al, 2019) and inadequate health literacy (Matchanova et al, 2021) as risk factors for lower self-efficacy for HCP interactions. Copyright © 2023 Association of Nurses in AIDS Care.…”
Section: Discussionsupporting
confidence: 92%
“…Even in milder forms, NCI is disabling and constitutes a public health issue due to its adverse effect on everyday functioning. NCI has been found to be associated with poor medication management [6], low selfefficacy for healthcare interactions [7], unemployment [8], poor health-related quality of life [9], and higher mortality [10].…”
Section: Introductionmentioning
confidence: 99%